Pengaruh Minat Belajar Terhadap Hasil Belajar Siswa Pada Pembelajaran Lari Jarak Pendek Kelas V Di SD Negeri 112 Seluma - Novriansyah, Fahrison; Suwarni, Suwarni; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the effect of interest in learning on student learning outcomes in class v short distance running at SD Negeri 112 Seluma. This research design uses a survey method with sampling techniques using total sampling with a sample size of 22 respondents, data analysis in this study using quantitative descriptive techniques with hypothesis testing using simple linear regression analysis. The variable value coefficient